Demographic trend and clinical features of brucellosis in patients with history of lower back pain - A study in tertiary care hospital - Dr Ravindra S Mohite; Dr Dhanashree P Inamdar; Dr V.A. Kulkarni; Dr. Pankaj Joshi; Dr R. D. Kulkarni (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Even though Lower Backpain (LBP) is the common symptom presenting to orthopedic OPD, not all the patients get relief from back pain. Due to complexity of the problem and heterogeneity of its nature many patients suffer from chronic lower back pain for long period. Infective agents do play a significant role in LBP and one of the differential diagnosis is Brucellosis. The present study is intended to find epidemiological correlation between brucellosis and LBP patients with pertinent serological tests and aid in decreasing morbidity associated with back pain. Materials and methods: Study involved evaluation of seventy adult patients (n=70) with history of low back pain attending orthopedic OPD. A detailed history of fever, work atmosphere, occupation in animal husbandry and ingestion of raw milk were collected and followed by radiological investigation (X-ray lower back). After physical examination serum samples were collected from these patients. First year MBBS students (n=30) without history of LBP were taken as controls. Results: Out of these 70 patients, seropositivity was seen in 10 patients by rapid slide agglutination test as screening procedure followed by tube agglutination test (SAT) as confirmatory test. Patients affected were men of 31 to 40 years age group. Incidence of brucellosis in our patients was 14.1%. Most of them were farmers by occupation. Of these 6 gave history of ingestion of raw milk. 6 patients had history of occupational exposure to animals and fever was seen in 5 cases. Radiological findings were positive in 4 patients. Conclusion: Diagnosing Brucellosis in patients with chronic backache is a challenge due to heterogeneity of condition. High clinical suspicion in patients with rural back ground, relevant serological tests with radiological evidence help in clinching the diagnosis of brucellosis in patients with chronic lower backpain.